Not in vain ; 21st what God hath wrought amongst the Kanakas being Report of the Solomon Island Branch and Twenty-first annual report of the Queensland Kanaka Mission for the year 1906-1907 (1907)
Contents includes : Queensland Kanaka Mission : Object and principles (revised).
Photocopy.
Keywords: Queensland Kanaka Mission; Queensland Kanaka Mission Solomon Island Branch; Brethren movement -- missions -- Australia -- history